2007
DOI: 10.2527/jas.2005-430
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and digestive effects of Neotyphodium coenophialum-infected tall fescue fed to lambs1

Abstract: The digestive responses and degradation of ergovaline and production of lysergic acid in the rumen of sheep offered Neotyphodium coenophialum-infected tall fescue straw at 2 ergovaline levels were investigated. Six crossbred wethers (56 +/- 3.0 kg of BW) were used in a randomized crossover design involving 2 treatments, for a total of 6 observations per treatment. The experiment consisted of two 28-d feeding periods with a 14-d washout period between them. The treatments were 1) tall fescue straw containing <0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 21 publications
2
42
0
Order By: Relevance
“…Recent data show that following ingestion of ergovaline-contaminated tall fescue straw, not only ergovaline, but also lysergic acid is detectable in the urine and faeces of exposed cattle. A mass-balance study revealed that the toxin concentration in ruminal fluid apparently increases over time (De Lorme et al 2007). These unexpected findings resulted in the hypothesis that the rumen fermentation processes can liberate non-extractable toxins (escaping the initial feed analysis) and metabolize ergovaline into lysergic acid that might be even be absorbed through the ruminal wall (Hill et al 2001).…”
Section: Clinical Mycotoxicoses In Dairy Cowsmentioning
confidence: 99%
“…Recent data show that following ingestion of ergovaline-contaminated tall fescue straw, not only ergovaline, but also lysergic acid is detectable in the urine and faeces of exposed cattle. A mass-balance study revealed that the toxin concentration in ruminal fluid apparently increases over time (De Lorme et al 2007). These unexpected findings resulted in the hypothesis that the rumen fermentation processes can liberate non-extractable toxins (escaping the initial feed analysis) and metabolize ergovaline into lysergic acid that might be even be absorbed through the ruminal wall (Hill et al 2001).…”
Section: Clinical Mycotoxicoses In Dairy Cowsmentioning
confidence: 99%
“…A series of in vivo alkaloid-balance studies all came to similar conclusions regarding the conversion of ergovaline to lysergic acid in geldings (Schultz et al 2006), wethers (De Lorme et al 2007) and steers (Merrill et al 2007). Specifically, these studies all reported intake concentrations of ergovaline and lysergic acid and concentrations of these compounds in the urine and faeces.…”
Section: Bioavailabilitymentioning
confidence: 76%
“…In that study (Goff et al 2012), the rates of ergovaline released from vegetative tissues would closely approximate reported dosage rates. In another in vitro rumen-fermentation study, only 60% of total ergot alkaloids were released (Stuedemann et al 1998) and an in vivo study with sheep reported a 64% (De Lorme et al 2007) apparent release of ergovaline from digested plant tissues. Differences between the in vitro studies of Goff et al (2012) and Stuedemann et al (1998) may related to differences in in vitro digestion methodology.…”
Section: Bioavailabilitymentioning
confidence: 94%
See 1 more Smart Citation
“…In addition to plantfungus-environment interaction variations, the grazing animal will also influence alkaloid production. Consumption of ergot alkaloid-containing feedstuff will interact with the gut microbiome prior to the animal and likely influences the level of exposure to ergot alkaloids by the animal (De Lorme et al, 2007;Ayers et al, 2009). Biological activity of ergot alkaloids absorbed by the animal is defined by the structural similarity of these compounds to biogenic amines (Berde, 1980) allowing ergot alkaloids to interact with serotonergic, adrenergic, and dopaminergic receptors that exist in varying populations throughout the body and results in variable negative effects.…”
mentioning
confidence: 99%